Non-axisymmetric dynamic response of imperfectly bonded buried orthotropic pipelines - Dwivedi J.P.; Mishra B.K.; Upadhyay P.C. (My University, 2025)
This paper deals with the non-axisymmetric dynamic response of an imperfectly bonded buried orthotropic pipeline subjected to longitudinal wave (P-wave) excitation. An infinite cylindrical shell model, including the rotary inertia and shear deformation effects, has been used for the pipeline. For some cases comparison of axisymmetric and non-axisymmetric responses have also been furnished.